2000
DOI: 10.1023/a:1008951632482
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Due to the uncertainty of the biologic plausibility of these associations and the possibility of alternative explanations, these results should be interpreted cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Moreover, it has been reported that exposure of pregnant rats to dioxin reduces AHR expression levels in the fetus [43]. In addition, it has been reported that children of parents with dioxin exposure may be at increased risk of NB [44]. In this study, we demonstrated an inverse relationship between AHR and MYCN expression both in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, it has been reported that exposure of pregnant rats to dioxin reduces AHR expression levels in the fetus [43]. In addition, it has been reported that children of parents with dioxin exposure may be at increased risk of NB [44]. In this study, we demonstrated an inverse relationship between AHR and MYCN expression both in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 62%
“…In studies that reported on maternal occupational exposures in pregnancy, positive associations have also been reported for exposure to acetone and insecticides and neuroblastoma (Kerr et al, 2000). Similar to the present study, no associations were previously observed with maternal occupational exposure to diesel fuel nor with maternal employment as a mechanic or service station attendant (De Roos et al, 2001; Olshan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…There are not previous reports, to our knowledge, of neuroblastoma in relation to PAH exposure. However, other studies have reported elevated effect estimates for maternal occupational exposures that involve PAH exposure, such as petroleum, creosote, and coal soot (Kerr et al, 2000). Its role as a developmental toxicant is supported by evidence that inhalation exposure of PAH causes reduced fetal growth and adduct formation in cord blood (Perera et al, 2005; Tang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignancies potentially associated with occupational coal tar pitch exposure include lung and prostate cancer in coke oven workers, lung cancer in foundry workers, lung and bladder cancer in aluminum smelter workers, and lung and stomach cancer in roofers (Harrison 2004). Other cancers suggested as being related to these compounds include renal cell carcinoma (Steineck et al 1989), neuroblastoma (following parental occupational exposure) (Kerr et al 2000), and non-Hodgkin lymphoma (Persson et al 1989). The International Agency for Research on Cancer (IARC) has concluded that there is “sufficient” evidence for coal tar pitch (IARC 1998a) to be considered carcinogenic in humans, but that creosotes (IARC 1998b) have only “limited evidence” for human carcinogenicity, despite demonstrating “sufficient” evidence to establish carcinogenicity in animals.…”
Section: Discussionmentioning
confidence: 99%